G113(P) Family and staff experiences of inpatient care for children with medical complexity. (May 2019) - Gannon, HL; Maechler, S; Butler, M
Abstract : Aims: To investigate the experiences of children with medical complexity (CMC), their families and the staff that care for them in an inpatient setting. Methods: We surveyed parents/carers of children under the care of multiple medical teams who were admitted to hospital for >7 days on a general ward of a tertiary children's hospital. We conducted questionnaires on experiences of care. We surveyed all eligible parents/carers and staff on our ward over a 2 week period. We intended to include children able to complete the questionnaire; however there were no eligible children during the study period able to do so. We also surveyed the multi-professional staff caring for these children. Results: We received responses from 14 parent/carers and 59 staff. Parent/Carer responses: Respondents highlighted the positive aspects of care they received; common themes expressed were the dedication, expertise and compassion of staff. 14/14 (100%) identified communication between specialities and multidisciplinary teams, as well as between staff and families, as an issue. 71% felt that being under more than one speciality caused problems. 28% felt that they were always given information in a way they understood. There were a number of suggestions for improvement: Common themes included joint consultations, keyworkers or allocated staff, more written information especially at the bedside, more formal updates or meetings. Staff responses: Staff shared many of the concerns of families; there was uncertainty about the plans for patients, and concerns about communication. 45% knew short-term plans 'some of the time' or 'never' 55% knew long-term plans 'some of the time' or 'never' 42% felt parents understood information given 'most of the time' Ideas on how this situation could be improved overlapped significantly with proposals from the family responses. Conclusion: CMC are an increasing part of the inpatient population, a trend which is likely to increase in all settings, but especially in tertiary hospitals. Our existing models of care do not always meet the needs of these children and families. We are piloting some of the interventions proposed by families and staff. We will continue to work with them to implement these changes and to improve further.